Finite element based simulation of electric field in high voltage power apparatus - Shangar Eagamathan. (2011)
High voltage equipment failures have been the core of numerous studies over the years. Currently, countless statistics are present that deals with failure causes of high voltage equipment. Unfortunately, these statistics do not provide adequate information on the real failure mechanism. This project aims to simulate electric field in high voltage power apparatus using finite element based method. The computer simulation program Ansoft Maxwell 3D was used to examine the field distribution on certain basic models to understand the relationship of geometry and electric field. The first modelling involved the manipulation of rod-plane gap and the effect of the electric field distribution on a rod. The program was then subsequently used to study the electric field distribution on high voltage bushing and then thereafter arriving at an optimized model based on theories made available by other research papers. This was followed by similar electric field simulation study on coaxial cylinders and spheres which are the basic building blocks of a knee connector; a high voltage direction divert equipment meant for bus bars.